Three Genetic Solutions for Travel Salesman problem - A., Hanan (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2017)
The classic Traveling Salesman Problem (TSP) has been frequently used as a test bed for the study of new local search techniques developed for general circuit-based permutation problems, local search heuristics for the traveling salesman problem (TSP) is chiefly based on algorithms using the classical Lin-Kernighan (L-K) procedure, La Lena simple genetic algorithm. This work give a detailed description of the three genetic solutions for this problem and found that genetic algorithms different in behavior according to the tour length.